Construct-Validating Humility: Perceptions of a Humble Doctor - Kim, Sang-Yeon; Sahlstein Parcell, Erin (Frontiers in Psychology, 2022)
Examining the nature of humility using self-report measures has been a challenging endeavor due to concerns of response biases and the common misconception that equates humility with self-deprecation. Alternatively, this study attempts to validate the construct of humility by assessing subjects’ (N = 553) response to a speech written to represent the core elements of humility as opposed to self-deprecation or unconditional self-underrating. Data show (a) humility comprises a latent construct subsuming accurate self-assessment, open-mindedness, and egalitarianism; and (b) humility outperforms self-deprecation in enhancing perceived sincerity, source credibility, and the intention to interact with the source. Results indicate, particularly for expert sources, humility cues can promote approachability while maintaining perceived expertise.